2020
DOI: 10.1111/jipb.12895
|View full text |Cite
|
Sign up to set email alerts
|

The roles of endomembrane trafficking in plant abiotic stress responses

Abstract: Endomembrane trafficking is a fundamental cellular process in all eukaryotic cells and its regulatory mechanisms have been extensively studied. In plants, the endomembrane trafficking system needs to be constantly adjusted to adapt to the ever-changing environment. Evidence has accumulated supporting the idea that endomembrane trafficking is tightly linked to stress signaling pathways to meet the demands of rapid changes in cellular processes and to ensure the correct delivery of stress-related cargo molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 90 publications
2
64
0
3
Order By: Relevance
“…Modeling of auxin-mediated polarization 14 has linked auxin feedback on PIN polarity to the auxin effect on PIN subcellular trafficking 15 17 . PM-associated PINs are internalized in clathrin-coated vesicles in a process called endocytosis 18 20 that might precede PIN relocation to different (plasma) membrane domains 21 , 22 . Numerous pharmacological and genetic determinants that impact on specific cellular events in the control of auxin transport have shaped our current picture of cellular mechanisms and crosstalk therein 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling of auxin-mediated polarization 14 has linked auxin feedback on PIN polarity to the auxin effect on PIN subcellular trafficking 15 17 . PM-associated PINs are internalized in clathrin-coated vesicles in a process called endocytosis 18 20 that might precede PIN relocation to different (plasma) membrane domains 21 , 22 . Numerous pharmacological and genetic determinants that impact on specific cellular events in the control of auxin transport have shaped our current picture of cellular mechanisms and crosstalk therein 1 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, treatment with the fungal toxin Brefeldin A (BFA) revealed the constitutive endocytic recycling of PIN proteins. This requires BFA-mediated interference of GNOM ARF-GEF activity, causing PM proteins, including PINs, to aggregate in cells 18,20 . Notably, auxin itself appears to inhibit the process of endocytosis and antagonize the BFA effect on PIN recycling 15 .…”
mentioning
confidence: 99%
“…Plants possess most canonical ESCRT components, which function in MVB biogenesis and MVB-mediated endosomal sorting (Valencia et al 2016;Gao et al 2017). However, emerging evidence indicates that unique ESCRT components have evolved in plants and these perform both conserved ESCRT-dependent cellular activities and plant-specific functions (Gao et al 2017;Wang et al 2019). For example, our and other studies have identified a plant-specific ESCRT component, FYVE DOMAIN PROTEIN REQUIRED FOR ENDO-SOMAL SORTING1 (FREE1), which localizes to MVBs by binding to MVB-enriched phosphatidylinositol-3-phosphate and interacts with several ESCRT subunits, including Vps23, BRO1-LIKE DOMAIN-CONTAINING PRO-TEIN/APOPTOSIS-LINKED GENE-2 INTERACTING PROTEIN X (AtBRO1/ALIX), and Snf7.…”
Section: Introductionmentioning
confidence: 99%
“…Salt can induce remodeling of spatially restricted clathrin-independent endocytic pathways in Arabidopsis root ( Baral et al., 2015 ). Endomembrane trafficking has a significant role in plant abiotic stresses ( Wang et al., 2020 ). For example, Golgi-localized cation/proton exchangers regulate ionic homeostasis and skotomorphogenesis in Arabidopsis ( Wang et al., 2018 ).…”
Section: Components Of Cellular and Physiological Features Of Root Hamentioning
confidence: 99%